Strategic Development Trends in the Automotive Industry of Ukraine - Nina Poyda-Nosyk; Robert Bacho (Engineering Proceedings)
This study delves into the strategic development trends within the automotive industry of Ukraine, aiming to provide a comprehensive understanding of the current landscape and anticipate future trajectories. The objectives of this research are twofold: firstly, to identify the key drivers shaping the evolution of the automotive industry in Ukraine; and secondly, to assess the strategic responses of industry stakeholders, including manufacturers, policymakers, and market participants, to these emergent trends. The study reveals several critical insights. Firstly, it identifies the growing significance of electric vehicles (EVs) and sustainable mobility solutions as a key trend, driven by both regulatory mandates and shifting consumer preferences. Secondly, it underscores the importance of innovation and technological integration, particularly in areas such as autonomous driving, connectivity, and digitalization. Thirdly, it highlights the strategic imperatives for Ukrainian automotive industry players to adapt to these trends, including investment in R&D, infrastructure development, and strategic partnerships. In conclusion, this study underscores the imperative for proactive strategic planning and adaptation to global trends towards sustainability, innovation, and digitalization within the Ukrainian automotive industry.